Corporate governance and firm performance: empirical evidence from emerging market - Balagobei, S. (AESS Publications, 2018)
Corporate governance (CG) has become a dominant theme in developed and developing countries. This study aims to investigate the impact of CG on firm performance of listed companies in Sri Lanka. Fifty listed companies were selected as a sample by using proportion random sampling method. Apart from that secondary data were collected from the annual report of listed companies in Sri Lanka from 2010 to 2015. This study considers the CG which is measured by board size, board independence, CEO duality, director’s ownership and audit committee as the independent variable while firm performance which is measured by ROA and Tobin’s Q as a dependent variable. Multiple regressions and Pearson’s correlation analyses were employed as the main tool of analyzing data. The results reveal that the board size and audit committee have significant impact on ROA and board size has significant impact on Tobin’s Q, whereas board independence, CEO duality and director’s ownership have insignificant impact on both firm performance measures such as ROA and Tobin’s Q. Furthermore the board size and audit committee have negative relationship with firm performance. This study suggests that small boards are associated with higher firm performance, possibly through closely monitored managements.
Keywords: Corporate governance; Firm performance; Board size; CEO Duality; Audit committee; ROA and Tobin’s Q